Towards better work : understanding labour in apparel global value chains - Rossi, Arianna; Luinstra, Amy; Pickles, John; SpringerLink (Online service). (London : Palgrave Macmillan UK, 2014)
Globalization of production has created opportunities and challenges for developing country producers and workers. This volume provides solutions-oriented approaches for promoting improved working conditions and labour rights in the apparel industry.
Keywords: Clothing workers -- Supply and demand; Manufacturing industries -- Employees -- Supply and demand